Wisata Hutan Bakau Kampung Kelembak - Jonathan Hanjaya; Stivani Ayuning Suwarlan; Victoria Victoria; Sherrin Tjandra; Audrey Audrey; Diani Diani; Kristin Kristin; Sarinah Sarinah; Herianto Herianto; Kelly Kelly (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Kelembak Village is a village located in Nongsa District that has potential and value to be a tourism area for local people and foreign tourists called Kelembak Cultural Tourism Village, where will be a tourist village with Malay culture in the 1960s era. The area of ​​Kelembak Village which is being developed into a tourism area is 6 hectares and the locations for the development of tourist area had been determined by residents but they do not have a tourist map to guide visitors on a tour and the purpose of the social activity is to make a Kelembak Village map as a guide for local people and foreign tourist.